Professionals in early childhood education and care systems European profiles and perspectives - Oberhuemer, Pamela; Schreyer, Inge 19XX-; Neuman, Michelle J. (Verlag Barbara Budrich, 2010)
In a European context of rapidly expanding early education/ care provision for young children, the staffing of these services is a critical quality issue. What are the requirements for professional education and training? How alike or how varied are the qualification profiles and fields of work? Through detailed country reports and comparative analyses across 27 countries, this book provides answers to these questions